Kesalahan Morfologis pada Penulisan Takarir Instagram @tereliyewriter - Nurjam’an, Muhammad Ichsan; Dewi, Septiyani; Dwiandini, Tazkia Aulia (ISOLEK: Jurnal Pendidikan, Pengajaran, Bahasa, dan Sastra, 2025)
This research is motivated by the prevalence of morphological errors in captions on the Instagram platform in the digital era. This study aims to describe the forms of morphological errors in captions of the @tereliyewriter account and explain the purpose of their use. The study used a qualitative descriptive method with human instruments and the Simak Bebas Libat Cakap (SLBC) technique. The research data consisted of 115 captions uploaded between October 1–15, 2025. Data collection was conducted through literature review, while data analysis used the Miles and Huberman model. The results showed 15 morphological errors and one spelling error. The most dominant error was incomplete reduplication. This incomplete form of reduplication reflects linguistic creativity in the digital space as part of the dynamics of language change in the social media user community.